Strong Convergence Analysis of Split-Step θ-Scheme for Nonlinear Stochastic Differential Equations with Jumps (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we investigate the mean-square convergence of the split-stepθ-scheme for nonlinear stochastic differential equations with jumps. Under some standardassumptions, we rigorously prove that the strong rate of convergence of the split-stepθ-scheme in strong sense is one half. Some numerical experiments are carried outto assert our theoretical result.